An outline of the professional quality of teachers who teach children with special needs - Darawsheh, Saddam Rateb; Asha, Intisar Khalil Khalil; AbuSaif, Radwan; Alhejoj, Arwa Faisal; Khasawneh, Mohamad Ahmad Saleem (Journal of Education and e-Learning Research, 2023)
The term "professional quality of life," sometimes abbreviated as "ProQOL," refers to an individual’s evaluation of the positive aspects of his or her working life. This frame may be categorized in two different ways. Compassion Fatigue (CF) is undesirable, yet Compassion Satisfaction (CS) motivates people to feel good about their job and, as a consequence, assist other people. Compassionate fulfillment is one of the most admirable qualities (CS). This study’s goal is to get a thorough understanding of ProQOL in the teaching profession for kids with special needs because the great majority of prior research on ProQOL was conducted on health professionals. This quantitative study did not use any type of experimental approach, yet it included the participation of 171 students with special needs educators. The obtained data indicate that teachers of students with special needs have a generally favorable perception regarding the environment in which they work. To provide one illustration: To mention one specific example, this does not always indicate that there are low incidences of STS or burnout. The majority of students with special needs teachers (77%) were operating at a level of burnout that was classified as Medium-High, and the majority of those instructors (72%) also had an STS level that was classified as Medium-High. The study recommended using the appropriate programs that raise the teachers’ professional levels to match the requirements of teaching students with special needs.